PENGARUH CASH TURNOVER, INVENTORY TURNOVER DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON ASSET PADA PT INDOFOOD SUKSES MAKMUR TBK PERIODE 2014-2023 - Amelia, Putri; Riyana Harjayanti, Diana (Journal of Research and Publication Innovation, 2024)
This research was conducted with the aim of finding out the partial and simultaneous influence of the variables Cash Turnover, Inventory Turnover and Debt to Equity Ratio on Return on Assets at PT Indofood Sukses Makmur Tbk for the 2014-2023 period. The research method used is a quantitative method with a quantitative descriptive research method. The data used in this research is secondary data in the form of financial reports sourced from the official website of PT Indofood Sukses Makmur Tbk and the Indonesian Stock Exchange. Data analysis techniques use descriptive statistical tests, classical assumption tests, simple and multiple regression analysis, partial and simultaneous hypothesis tests, coefficient of determination analysis, and correlation coefficient tests using SPSS version 26. Based on the partial test, the Cash Turnover variable has no significant effect on Return On Assets with a tcount<ttable value of 0.373<2.447 and a significance value of 0.72>0.05. Partially, the Inventory Turnover variable has no significant effect on Return On Assets with a tcount<ttable value of -0.398<2.447 and a significance value of 0.70>0.05. Partially, the Debt to Equity Ratio variable has no significant effect on Return On Assets with a tcount<ttable value of –1.323<2.447 and a significance value of 0.22>0.05. Simultaneously, Cash Turnover, Inventory Turnover and Debt to Equity Ratio do not have a significant effect on Return On Assets with a Fcount<Ftable value of 0.481<4.757 and a significance value of 0.71>0.05.